2010
DOI: 10.1007/s00441-010-0961-0
|View full text |Cite
|
Sign up to set email alerts
|

GTPases RhoA and Rac1 are important for amelogenin and DSPP expression during differentiation of ameloblasts and odontoblasts

Abstract: Morphogenesis and cytodifferentiation are distinct processes in tooth development. Cell proliferation predominates in morphogenesis; differentiation involves changes in form and gene expression. The cytoskeleton is essential for both processes, being regulated by Rho GTPases. The aim of this study was to verify the expression, distribution, and role of Rho GTPases in ameloblasts and odontoblasts during tooth development in correlation with actin and tubulin arrangements and amelogenin and dentin sialophosphopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 57 publications
3
32
1
3
Order By: Relevance
“…RhoA and ROCK mRNA levels were recently reported to be elevated in WT rat first molars at PN5 [Biz et al, 2010], and we have observed a similar elevation in murine molars (not shown). Because the Rho dissociation inhibitor RhoGDI, which sequesters Rho to control its status, decreases shortly after birth [Hatakeyama et al, 2009], this pathway fluctuates exactly as the ameloblast cells undergo changes in structural/functional relationships.…”
Section: Discussionsupporting
confidence: 70%
“…RhoA and ROCK mRNA levels were recently reported to be elevated in WT rat first molars at PN5 [Biz et al, 2010], and we have observed a similar elevation in murine molars (not shown). Because the Rho dissociation inhibitor RhoGDI, which sequesters Rho to control its status, decreases shortly after birth [Hatakeyama et al, 2009], this pathway fluctuates exactly as the ameloblast cells undergo changes in structural/functional relationships.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, the Rho family inhibitor RhoGDI was downregulated during ameloblast secretory stage (24). Interestingly, expression of RhoA, the direct upstream activator of ROCK, and ROCK1 were also detected strongly in highly polarized ameloblasts, but weakly in non-polarized cells of inner epithelium and dental papilla during tooth development (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…RhoA also regulates the expression of amelogenin and DSPP during cytodifferentiation of ameloblasts and odontoblasts, respectively (10). However, the regulation of Rock1 expression has not been investigated, although the activators of Rock1 have been widely discussed.…”
mentioning
confidence: 99%
“…Further, they are involved in osteoclastogenesis as well as in hematopoiesis and hemopathies [12], [13]. Recently, evidence has emerged showing the involvement of Rho signaling in tooth development [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24]. In this article, we summarize some interesting recent findings that provide molecular insights into how signaling by Rho GTPases results in tooth development, focusing on ameloblast differentiation in particular.…”
Section: Introductionmentioning
confidence: 99%